Early predicting brain metastases of EGFR positive lung adenocarcinoma patients by CT radiomics - Xinliu He; Chao Guan; Ting Chen; Houde Wu; Liuchao Su; Mingfang Zhao; Li Guo (Physical and Engineering Sciences in Medicine, 2026)

Effectiveness of Salicornia europaea-Derived Biochar in Immobilizing Cadmium in Acidic Soil - Shaoqing Ge; Lei Wang; Mingfang Hu; Zhenyong Zhao; Changyan Tian (Journal of Soil Science and Plant Nutrition, 2025)

The 3PM transformation potential of minimal residual disease in solid tumor management: a bibliometric analysis and review - Yining Chen; Xin Li; Suya Zhao; Yuchong Zhang; Haixu Wang; Fangjian Na; Qi Guan; Zhi Li; Heming Li; Mingfang Zhao (EPMA Journal, 2025)

Effects of halophyte Suaeda salsa continuous cropping on physical and chemical properties of saline soil under drip irrigation in arid regions - Sihai Liu; Ning Wang; Dongze Li; Changyan Tian; Ke Zhang; Mingfang Hu; Haishan Niu; Zhenyong Zhao (Agriculture, Ecosystems & Environment, 2024)

The first detection of mpox virus DNA from wastewater in China - Jin Xu; Chao Liu; Qun Zhang; Haining Zhu; Feng Cui; Zhiqiang Zhao; Mingfang Song; Bo Zhou; Yunxiao Zhang; Peilong Hu; Lei Li; Qin Wang; et al. (Science of The Total Environment, 2024)

Dual purpose ratooned rice improves agri-food production with reduced environmental cost - Deqiang Qi; Ke Liu; Mingfang Fu; Matthew Tom Harrison; Xiaofei Shi; Xiangchen Liu; Peter de Voil; Yunbo Zhang; Ando Radanielson; Wenge Wu; Jingrui Chen; Yu Jiang; et al. (Journal of Cleaner Production, 2024)

Steric heights of submesoscale processes and internal gravity waves in the subtropical northwestern Pacific and northern South China Sea as revealed by moored observations - Mingfang Miao; Zhiwei Zhang; Jinchao Zhang; Yue Wang; Wei Zhao; Jiwei Tian (Progress in Oceanography, 2023)

Allelic variations of ClACO gene improve nitrogen uptake via ethylene-mediated root architecture in watermelon - Kejia Zhang; Wei Gao; Yimei Zhou; Haoshun Zhao; Yuelin Xia; Mengyi Zhang; Yongming Bo; Xiaolong Lyu; Zhongyuan Hu; Jinghua Yang; Mingfang Zhang (Theoretical and Applied Genetics, 2023)

Correction to: Dietary supplementation with synbiotics improves growth performance, antioxidant status, immune function, and intestinal barrier function in broilers subjected to cyclic heat stress - Mingfang Du; Yefei Cheng; Yueping Chen; Shiqi Wang; Haoran Zhao; Chao Wen; Yanmin Zhou (Environmental Science and Pollution Research, 2022)

Dietary supplementation with synbiotics improves growth performance, antioxidant status, immune function, and intestinal barrier function in broilers subjected to cyclic heat stress - Mingfang Du; Yefei Cheng; Yueping Chen; Shiqi Wang; Haoran Zhao; Chao Wen; Yanmin Zhou (Environmental Science and Pollution Research, 2022)

An allelic variant in the ACS7 gene promotes primary root growth in watermelon - Ahmed Mahmoud; Rui Qi; Haoshun Zhao; Haiyang Yang; Nanqiao Liao; Abid Ali; Guy Kateta Malangisha; Yuyuan Ma; Kejia Zhang; Yimei Zhou; Yuelin Xia; Xiaolong Lyu; et al. (Theoretical and Applied Genetics, 2022)

Application of galactinol to tomato enhances tolerance to cold and heat stresses - Yudong Liu; Li Zhang; Jian Ma; Sida Meng; Chunpeng Pang; Xiaomeng Zhao; Huidong Zhang; Shou Wang; Tao Xu; Yi He; Yufeng Liu; Mingfang Qi (Horticulture, Environment, and Biotechnology, 2022)

Effects of light intensity on Opsin4 , Opsin5, and Pax6 expressions of the sea urchin Strongylocentrotus intermedius - Mingfang Yang; Yushi Yu; Jingyun Ding; Jia Luo; Jiangnan Sun; Fangyuan Hu; Yaqing Chang; Chong Zhao (Marine Ecology, 2020)
The detection of light intensity and subsequent phototaxis are essential for the fitness of sea urchins in intertidal and shallow subtidal waters, where light intensity varies in accordance with the depth and other hydrographic conditions. The molecular basis of photoresponse, however, remains largely unknown. We compared the expression of SiOpsin4 , SiPax6, and SiOpsin5 among tube feet, coelomocytes, gonads, and gut of the sea urchin Strongylocentrotus intermedius . All three genes showed the significantly highest expression in tube feet. To test whether r‐opsin genes (for example, Opsin4 ) and Pax6 in tube feet, rather than chaopsin genes (for example, Opsin5 ), are involved in the molecular responses to light intensity, we investigated the expression of Opsin4 , Pax6, and Opsin5 among four light intensities. Both Opsin4 and Pax6 expressions were significantly higher in the sea urchins at 1,500 lx than at 100, 300, and 700 lx, indicating a co‐upregulation of Opsin4 and Pax6 expressions in sea urchins exposed to the high light intensity (for example, 1,500 lx). However, there was no significant difference of SiOpsin5 expression among the four light intensity groups. Consistent with our hypothesis, there was no significant difference in either Opsin4 or Pax6 expression between the two light intensity environments (low light intensity environment: 50–100 lx; high light intensity environment: 330–1400 lx). This indicates that positive phototaxis and negative phototaxis probably regulate the expression of Opsin4 and Pax6 to a similar level when sea urchins are exposed to the high and low light intensities, respectively. The present study provides new insights into the molecular basis of light intensity detection and subsequent phototaxis of eyeless species.

Development and Characterization of a Neutralizing Anti-idiotype Antibody Against Mirvetuximab for Analysis of Clinical Samples - Sven Loebrich; Mingfang Shen; Erika Cohen; Gillian Payne; Ying Chen; Megan Bogalhas; Yiwei Zhao (The AAPS Journal, 2017)

Virus-induced gene silencing for comparative functional studies in Gladiolus hybridus - Xionghui Zhong; Xue Yuan; Ze Wu; Muhammad Ali Khan; Jin Chen; Xiaoxin Li; Benhe Gong; Yang Zhao; Jian Wu; Chenyu Wu; Mingfang Yi (Plant Cell Reports, 2014)

Involvement of Ca2+ and CaM3 in Regulation of Thermotolerance in Lily (Lilium longiflorum) - Xing Cao; Jin Yi; Ze Wu; Xian Luo; Xionghui Zhong; Jian Wu; Muhammad Ali Khan; Yang Zhao; Mingfang Yi (Plant Molecular Biology Reporter, 2013)